A wafer-scale fabrication method for three-dimensional plasmonic hollow nanopillars. Issue 17 (29th July 2021) - Jonker, D.; Jafari, Z.; Winczewski, J. P.; Eyovge, C.; Berenschot, J. W.; Tas, N. R.; Gardeniers, J. G. E.; De Leon, I.; Susarrey-Arce, A.
Abstract : Access to a wafer-scale nanofabrication strategy for crafting three-dimensional plasmonic structures. Abstract : Access to nanofabrication strategies for crafting three-dimensional plasmonic structures is limited. In this work, a fabrication strategy to produce 3D plasmonic hollow nanopillars (HNPs) using Talbot lithography and I-line photolithography is introduced. This method is named subtractive hybrid lithography (SHL), and permits intermixed usage of nano-and-macroscale patterns. Sputter-redeposition of gold (Au) on the SHL resist pattern yields large areas of dense periodic Au-HNPs. These Au-HNPs are arranged in a square unit cell with a 250 nm pitch. The carefully controlled fabrication process resulted in Au-HNPs with nanoscale dimensions over the Au-HNP dimensions such as an 80 ± 2 nm thick solid base with a 133 ± 4 nm diameter, and a 170 ± 10 nm high nano-rim with a 14 ± 3 nm sidewall rim-thickness. The plasmonic optical response is assessed with FDTD-modeling and reveals that the highest field enhancement is at the top of the hollow nanopillar rim. The modeled field enhancement factor (EF) is compared to the experimental analytical field enhancement factor, which shows to pair up with ca. 10 3 < EF < 10 4 and ca. 10 3 < EF < 10 5 for excitation wavelengths of 633 and 785 nm. From a broader perspective, our results can stimulate the use of Au-HNPs in the fields of plasmonic sensors and spectroscopy.